SISTEM PENYIRAMAN BUDIDAYA TANAMAN CABAI BERDASARKAN PENGUKURAN SUHU DAN KELEMBABAN TANAH - Puji Lestari; Tasmi; Fery Antony (Journal Of Intelligent Networks and IoT Global, 2023)
The process of growing peppers requires extra attention important to maintaining soil moisture. The intensity of temperature and humidity in chili plants can make it easier for farmers to measure soil conditions and make it easier for farmers to monitor the quality of the chili they grow. In this study, the progression of an Internet of Things (IoT)-based system was performed out. To monitor and find out the temperature and humidity and can carry out the plant watering system automatically. NodeMcu ESp32 microcontroller as a data center, with temperature values taken from DHT11 sensors and humidity values from Soil Moisture sensors. This soil moisture control system works at temperatures of more than 20°C and humidity levels of more than 70% so that the system can control the water pump according to the measured level of soil moisture. From the results of experiments that have been carried out testing chili plants with a Soil Moisture sensor, the dry soil output value is >=70% with a temperature from the DHT11 sensor of 33.30 °C and a wet soil output value of <=60% with a temperature from the DHT11 sensor of 29.00°C has an accurate value with what has been tested with several conditions that have been made previously